"AN ANALYSIS OF EXCHANGE PATTERNS BETWEEN TEACHER AND STUDENTS IN ENGLISH CLASSROOM (A STUDY OF CLASSROOM DISCOURSE ANALYSIS OF TEACHER IN SMAN 13 BANDUNG)." - Gilang Rajasa, - (2008)
The title of the research is "An Analysis of Exchange Patterns between Teacher and Students in English Classroom (A study of classroom discourse analysis of teacher in SMAN 13 Bandung)." The aims of this study are to find out the variation of exchange patterns in teacher-students interaction and to investigate the effects of the difference of teacher's cultural background on variation of exchange patterns in the teacher-students interaction in English classroom. The writer conducted the qualitative research method. Moreover, this research produces data to support research questions. The first grade class of SMAN 13 Bandung is the object of the research. The data were obtained from 3 x 90 minute (3 times) classroom video recording, classroom observation, interviewing the teacher, distributing questionnaire to the students, and collecting document (lesson plan). There were four steps in analyzing the effects of the difference of teacher's cultural background in teacher-students interaction: transcribing, coding, comparing, and interpreting the data. The findings show that the use of exchange patterns in teacher-students interaction in English classroom is dominated by the teacher. In this study, non-anomalous exchanges appear more than anomalous exchanges. It means that the teacher does a usual conversation among the students in the classroom. Meanwhile, the difference of teacher's cultural background in teacher-students in English classroom did not appear in this study. It is because the teacher is a quick learner (showed in the interview) in a new environment.